"The Therapy of Elimination First" for Early Acute Mastitis: A Systematic Review and Meta-Analysis. (2nd May 2018) - Zhang, Ying; Sun, Xiaoying; Li, Kexin; Wang, Xiaomin; Cai, Lijun; Li, Xin; Zhou, Min
Abstract : We evaluated the effectiveness of "the therapy of elimination first" in early acute mastitis, using four databases (CNKI, Wanfang, Embase, and PubMed). The study incorporated 2508 patients from 16 randomized controlled trials (RCTs). Included trials used Chinese oral medicine and applied the principle of "Eliminating Therapy" for the early treatment of acute mastitis, with simple antibiotic treatment as a control group. Meta-analysis showed significant differences between the overall effectiveness of oral Chinese medicine using Eliminating Therapy (OCM-ET) and western medicine using antibiotics (WM-A) (odds ratio [OR] = 4.43, 95% confidence interval [CI] = 3.21–6.12, Z = 9.04, and P < 0.00001 ). Analysis of subgroups based on the use of classic or self-made preparations of the medicines showed smaller statistical heterogeneity among the different subgroups (P > 0.05, I 2 ≤ 50 %). The OCM-ET group showed significantly shorter pain relief times [mean difference (MD) = −3.08, 95% CI = (−5.90, −0.26), and P = 0.03 ] and cure times [MD = −6.27, 95% CI = (−9.68, −2.85), and P = 0.0003 ] than did the WM-A group. Our findings suggest that OCM-ET can shorten the duration of pain and improve cure time in early acute mastitis patients, with fewer adverse reactions. However, RCTs of higher quality with larger sample sizes are required to confirm these findings.